ГЕОМЕТРИЧНІ ДЕКОРАТИВНІ ОРНАМЕНТИ МЕТОДАМИ КРЕСЛЕННЯ З ВИКОРИСТАННЯМ КОМП'ЮТЕРНИХ ТЕХНОЛОГІЙ (Педагогіка вищої та середньої школи, 2008)
Geometrical decorative ornamental pattern by drawing methods using computer technologies. Some kinds of round and ribbon ornamental pattern, at the heart of which are the compasses couplings without the procedure of couplings' constructions, and also using computer technologies for ornamental pattern's creation were examined in the article.